APPLICATION OF TRAINING AND PRACTICE METHODS IN CALLIGRAPHY LEARNING TO IMPROVE ARABIC WRITING IN GRADE TEN AT AL-FAIZ ISLAMIC BOARDING SCHOOL IN MEDAN - Mellani, Mellani; Kamalia, Kamalia (Universitas Islam Negeri Sumatera Utara Medan, 2025)
In education, teachers play a very important role in designing learning activities to engage students and ensure that learning objectives are conveyed effectively. The purpose of this study was to determine the development of Arabic writing in students studying calligraphy. This study was conducted at the Al-Faiz Islamic boarding school in Medan. In this study, the researcher used a qualitative research method with a descriptive approach and data collection techniques in the form of observation and interviews. Observations were conducted on twenty female students in grade X at the Al-Faiz Islamic Boarding School in Medan. Based on an interview with calligraphy teacher Ustadz Abimanyu,